Warm perineal compresses during the second stage of labor for reducing perineal trauma: A meta-analysis. (September 2019) - Magoga, Giulia; Saccone, Gabriele; Al-Kouatly, Huda B.; Dahlen G, Hannah; Thornton, Charlene; Akbarzadeh, Marzieh; Ozcan, Tulin; Berghella, Vincenzo
Abstract: Objective: Perineal trauma may have a negative impact on women's lives as it has been associated with perineal pain, urinary incontinence and sexual dysfunction. The aim of this systematic review and meta-analysis of randomized controlled trials was to evaluate the effectiveness of warm compresses during the second stage of labor in reducing perineal trauma. Methods: Electronic databases were searched from inception of each database to May 2019. Inclusion criteria were randomized trials comparing warm compresses (i.e. intervention group) with no warm compresses (i.e. control group) during the second stage of labor. Types of participants included pregnant women planning to have a spontaneous vaginal birth at term with a singleton in a cephalic presentation. The primary outcome was the incidence of intact perineum. Meta-analysis was performed using the Cochrane Collaboration methodology with results being reported as relative risk (RR) with 95% confidence interval (CI). Results: Seven trials, including 2103 participants, were included in this meta-analysis. Women assigned to the intervention group received warm compresses made from clean washcloths or perineal pads immersed in warm tap water. These were held against the woman's perineum during and in between pushes in second stage. Warm compresses usually started when the baby's head began to distend the perineum or when there was active fetal descent in the second stage of labor. We found a higher rate of intact perineum in the intervention group compared to the control group (22.4% vs 15.4%; RR 1.46, 95% CI 1.22 to 1.74); a lower rate of third degree tears (1.9% vs 5.0%; RR 0.38, 95% CI 0.22 to 0.64), fourth degree tears (0.0% vs 0.9%; RR 0.11, 95% CI 0.01 to 0.86) third and fourth degree tears combined (1.9% vs 5.8%; RR 0.34, 95% CI 0.20 to 0.56) and episiotomy (10.4% vs 17.1%; RR 0.61, 95% CI 0.51 to 0.74). Conclusion: Warm compresses applied during the second stage of labor increase the incidence of intact perineum and lower the risk of episiotomy and severe perineal trauma.